Factors determining homocysteine levels in Russian patients with stable coronary heart disease - O. O. Shakhmatova; A. L. Komarov; D. V. Rebrikov; M. A. Turchaninova; T. I. Kotkina; A. V. Bolvacheva; A. D. Deev; A. B. Dobrovolsky; E. V. Titaeva; E. A. Panchenko (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To identify the factors determining homocysteine (HMC) levels in Russian patients with stable coronary heart disease (CHD). Material and methods. The study included 506 patients (388 men; mean age 59,4±12,2 years) with stable CHD. Classical risk factors (RFs) of cardiovascular disease (CVD), renal function (creatinine clearance by Cockroft-Gault formula), and atherosclerotic pathology of other localizations were assessed. The levels of plasma HMC, folate, and cobalamin were measured. Genetic analysis was performed using the real-time polymerase chain reaction method. Results. In 432 patients (85,4 %), hyperhomocysteinemia was diagnosed. The mean HMC level was 14,3±4,6 mkmol/l. According to multifactor analysis results, HMC level was independently associated with folate level (beta coefficient -3,86, p<0,0001), cobalamin level (beta -5,73, p<0,0001), and MTRR 66AA genotype (beta 10,71, p<0,0005). In addition, HMC concentration was linked to the following combinations: MTRR 66G allele + folate level (beta 1,12, p<0,0001), MTRR 66AA allele + cobalamin level (beta 0,012, p<0,0001), TCN 776G allele + cobalamin level (beta -0,03, p<0,0001), TCN 776G allele + folate level (beta 0,58, p<0,0009), MTR 2756G allele + cobalamin level (beta 0,004, p<0,002), MTRR 66G allele + creatinine clearance <90 ml/min (beta 0,08, p<0,001), and TCN 776G allele + creatinine clearance <90 ml/min (beta 0,07, p<0,0007). Conclusion. In Russian patients with stable CHD, HMC level was associated with folate and cobalamin concentrations and MTRR 66AA genotype, as well as with MTR 2756G, MTRR 66G, and TCN 776G alleles combined with vitamin concentrations and renal function.